Poly[N‐(2‐hydroxypropyl)methacrylamide]‐Modified Magnetic γ‐F2O3 Nanoparticles Conjugated with Doxorubicin for Glioblastoma Treatment. (12th November 2019) - Plichta, Zdeněk; Horák, Daniel; Mareková, Dana; Turnovcová, Karolína; Kaiser, Radek; Jendelová, Pavla
Abstract: With the aim to develop a new anticancer agent, we prepared poly[ N ‐(2‐hydroxypropyl)methacrylamide‐ co ‐methyl 2‐methacrylamidoacetate] [P(HP‐MMAA)], which was reacted with hydrazine to poly[ N ‐(2‐hydroxypropyl)methacrylamide‐ co ‐ N ‐(2‐hydrazinyl‐2‐oxoethyl)methacrylamide] [P(HP‐MAH)] to conjugate doxorubicin (Dox) via hydrazone bond. The resulting P(HP‐MAH)‐Dox conjugate was used as a coating of magnetic γ‐Fe2 O3 nanoparticles obtained by the coprecipitation method. In vitro toxicity of various concentrations of Dox, P(HP‐MAH)‐Dox, and γ‐Fe2 O3 @P(HP‐MAH)‐Dox nanoparticles was determined on somatic healthy cells (human bone marrow stromal cells hMSC), human glioblastoma line (GaMG), and primary human glioblastoma (GBM) cells isolated from GBM patients both at a short and prolonged exposition time (up to 7 days). Due to hydrolysis of the hydrazone bond in acid milieu of tumor cells and Dox release, the γ‐Fe2 O3 @P(HP‐MAH)‐Dox nanoparticles significantly decreased the GaMG and GBM cell growth compared to free Dox and P(HP‐MAH)‐Dox in low concentration (10 nM), whereas in hMSCs it remained without effect. γ‐F2 O3 @PHP nanoparticles alone did not affect the viability of any of the tested cells. Abstract : Doxorubicin (DOX) was conjugated via a degradable hydrazone bond to poly[ N ‐(2‐hydroxypropyl)methacrylamide] (PHP)‐coated maghemite nanoparticles, which significantly decreased cell growth of human glioblastoma cells. The particles can be thus suggested as a promising new anticancer agent.